CORRELATION OF DENGUE VIRUS SEROTYPE AND DVI SEVERITY IN ADULT PATIENTS - Suci Andriani; Aryati Aryati; Usman Hadi (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2018)
The clinical manifestation of dengue virus infection is often not clear, varies widely from mild to severe. Exposure of dengue virus which serotype is different from a previous infection is a risk factor for the severe manifestation of dengue virus infection. Dengue hemorrhagic fever is classified into four degrees of severity based on clinical manifestations and laboratory results. Real-time RT-PCR Dengue can detect dengue virus serotype in early dengue virus infection. The aimed of this study was to prove the correlation between dengue virus serotype and degree of severity in adult patients. This study was a cross-sectional observational design done in February until July 2016. Subjects consisted of 100 dengue virus infection patients. Serum of the patients was examined using Real-time RT-PCR Dengue (Simplexa™ Dengue). It was shown that from 46 patients with DENV-3 serotype was 63%, DENV-2 serotype 17.4%, DENV-1 serotypes 17.4% and mixed infection of DENV-1 and DENV-3 serotype 2.2%. There was not any DENV-4 serotype. Dengue Hemorrhagic Fever (DHF) stage I was 47.8%, DHF stage II was 30.4%, DHF stage III was 10.9% and Dengue Fever was 10.9%. There was not any DHF stage IV. There was not enough evidence that DENV-3 correlated with the degree of severity (p= 0.510). Based on this research, DENV-3 serotype was the dominant serotype prevalent at the Dr. Soetomo Hospital. There was no correlation between viral dengue serotype and severity in dengue adult patients in this study.